Failure modes of steel beams with web openings - Ranisavljević Maja; Dobrić Jelena (Građevinski Materijali i Konstrukcije)
As an alternative to trusses and open-web joist systems, beams with Web openings are lightweight, long-spanning structural elements that bind structural role (efficient load distribution) and functionality in a visually acceptable way by allowing service routes to be installed within their cross-section height. Owing to its specific production process, this beam type has a beneficial impact on rational use of material for low-carbon structures. In recent years, extensive scientific research has been conducted to assess the structural behavior and ultimate capacity of beams with Web openings. Due to the presence of Web openings, load transfer is accompanied by complex stress distributions in the section Web, causing failure modes that are distinguishable from those of solid I-section beams. This paper summarizes the different failure modes of the beams with Web openings that have been discovered and confirmed in numerous experiments of reference scientific researches. Based on the state-of-the art in this structural area, the predictions of different failure modes that are affected by influencing geometric parameters are provided.